DEVELOPMENT OF LEGAL CONSCIOUSNESS AND CULTURE OF YOUNG PEOPLE - Abdurakhmanova Nodirahan Husnutdinovna (Modern American Journals, 2025)
This interdisciplinary study navigates the landscape of legal consciousness and cultural integration among young people. Combining qualitative insights, quantitative data, community engagement initiatives, and educational reforms, the research unravels the complex interplay between legal knowledge, cultural influences, and development strategies. Findings showcase disparities in legal knowledge across educational levels, affirming the positive correlation between legal awareness and confidence in legal institutions. Community engagement emerges as a potent catalyst, while educational reforms demonstrate transformative impacts on legal knowledge and attitudes. These insights inform actionable strategies for policymakers, educators, and community leaders to nurture informed, engaged, and culturally-sensitive young citizens.
Keywords: Legal consciousness, cultural integration, youth development, educational reforms, community engagement, legal knowledge.